Effect of Extraction Time and Solvent Power on Phytochemical Screening and Antioxidant Activity of Momordica charantia L. Fruit Extracts - Malik, Rayees Ahmad; Saad, Mabroukah Massuod; Tiwari, Surabhi (Asian Journal of Chemistry, 2019)
This work reports the analysis of phytochemical screening and antioxidant activity of Momordica charantia L. fruit extracts at different extraction conditions. The standard procedures are achieved by ferric reducing antioxidant, nitric oxide scavenging assay methods. Extraction under different maceration periods viz. 6, 12, 24 and 48 h organic solvent especially ethanol was found more effective followed by water extract, acetone and ethyl acetate. The maximum number of phytochemicals were observed at 12 h followed by 6 h. Hence, the medium time duration influences the extraction of phytochemicals at 12, 6 h rather than 24 and 48 h. The ferric reducing antioxidant activity was observed maximum at 12 h (0.156 ± 0.012, 79.31 %) followed by 6 h (0.149 ± 0.022, 71.26 %), 24 h (0.143 ± 0.032, 64.36 %) and 48 h (0.139 ± 0.023, 59.77 %) in ethanolic extract. Similarly the nitric oxide scavenging activity was observed maximum at 12 h (0.093 ± 0.023, 76.53 %) followed by 6 h (0.113 ± 0.043, 71.17 %), 24 h (0.134 ± 0.031, 65.81 %) and 48 h (0.161 ± 0.053, 58.92 %) in ethanolic extract followed by aqueous, acetone, ethyl acetate, petroleum ether and hexane extracts at 12 h with respect to standard (ascorbic acid). The results show that the ethanol is more effective for extraction of phytochemicals followed by water extract. The maximum number of phytochemicals are obtained at medium time duration (12 h) in ethanolic extract. Hence demonstrates that fruit extracts are important sources of natural antioxidant agents.